Author Correction: HIV-1 Transmissions Among Recently Infected Individuals in Southwest China are Predominantly Derived from Circulating Local Strains. Issue 1 (December 2018) - Li, Jianjun; Feng, Yi; Shen, Zhiyong; Li, Yingxin; Tang, Zhenzhu; Xiong, Runsong; Zhang, Hongman; Wei, Jing; Zhou, Xinjuan; Deng, Yueqin; Fang, Ningye; Lan, Guanghua; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.